2016
DOI: 10.1002/iub.1521
|View full text |Cite
|
Sign up to set email alerts
|

Association of theAURKAandAURKCgene polymorphisms with an increased risk of gastric cancer

Abstract: Single nucleotide polymorphisms (SNPs) in mitotic checkpoint genes can contribute to susceptibility of human cancer, including gastric cancer (GC). We aimed to investigate the effects of Aurora kinase A (AURKA), Aurora kinase B (AURKB), and Aurora kinase C (AURKC) gene polymorphisms on GC risk in Slovenian population. We genotyped four SNPs in AURKA (rs2273535 and rs1047972), AURKB (rs2241909), and AURKC (rs758099) in a total of 128 GC patients and 372 healthy controls using TaqMan allelic discrimination assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…Analysis of AURKA haplotypes demonstrated that the frequency of G rs911160 ‐C rs1047972 ‐T rs2273535 haplotype was significantly higher in patients when compared to the control group, highlighting significant effects of this haplotype on increased risk of stomach cancer development. These findings confirmed the results obtained by individual analysis of polymorphisms in AURKA mitotic gene [Mesic et al, ]. In silico analysis of rs911160 revealed that in the presence of the minor C allele, additional NF‐Y, NF‐1 and NFI‐CTF binding motifs were recognized.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Analysis of AURKA haplotypes demonstrated that the frequency of G rs911160 ‐C rs1047972 ‐T rs2273535 haplotype was significantly higher in patients when compared to the control group, highlighting significant effects of this haplotype on increased risk of stomach cancer development. These findings confirmed the results obtained by individual analysis of polymorphisms in AURKA mitotic gene [Mesic et al, ]. In silico analysis of rs911160 revealed that in the presence of the minor C allele, additional NF‐Y, NF‐1 and NFI‐CTF binding motifs were recognized.…”
Section: Discussionsupporting
confidence: 88%
“…These variants were associated with reduced risk for the development of diffuse type, increased survival, and decreased probability for the development of poorly differentiated adenocarcinoma [Bao et al, 2016]. Two previous studies also revealed significant associations between genotypes of rs758099 in mitotic kinase AURKC and rs151658 in mitotic kinase TTK and histopathological variables of patients, including Lauren classification and the degree of differentiation Mesic et al, 2016]. Analysis of AURKA haplotypes demonstrated that the frequency of G rs911160 -C rs1047972 -T rs2273535 haplotype was significantly higher in patients when compared to the control group, highlighting significant effects of this haplotype on increased risk of stomach cancer development.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Aurora kinase family is comprised regulators controlling chromosome segregation and condensation, centrosome duplication, G2/M transition, kinetochore attachment, and cytokinesis [12]. Three types of Aurora kinases are present in mammalian cells, AURKA, AURKB, and AURKC which have specific subcellular localizations and functions during the cell cycle.…”
Section: Introductionmentioning
confidence: 99%